PENGGUNAAN VIDEO YOUTUBE SEBAGAI MEDIA PENGAJARAN PADA MATA KULIAH SPEAKING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA MAHASISWA BAHASA INGGRIS DI STKIP MUHAMMADIYAH MANOKWARI - Syahira Syahira (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to improve speaking skills in second semester students of the English education study program by using youtube videos. The method used in this research is descriptive qualitative. The subjects of this research are second semester students of the English Education Study Program for the 2021/2022 academic year. Data collection techniques in this study were observation, interviews, tests, and documentation. Aspects of assessment in speaking skills are divided into five aspects, namely Fluency, Grammar, Pronunciation, Intonation and Performance/Acting. The results of the study were obtained as follows. The ability of students to speak in groups on the Fluency aspect is 63.6%, Grammar 68%, Pronunciation 66%, Intonation 80% and Performance or Acting 82%